(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Textile is certainly a complex multi-pore structure, which can be described as parallel pore structure or pellets accumulation pore structure. The heat and moisture transfer through textile is affected by its structure. Based on the parallel pore structure of textile and a system of human-textile-environment, this paper reports a model of heat and moisture transfer through parallel pore textiles. It is a system of coupled ordinary differential equations on temperature, water vapor pressure and water vapor mass flux through textile and condensation on the surface of textile. By solving the coupled ordinary differential equations, three formulae are acquired to describe temperature, water vapor pressure from human skin surface to environment and water vapor transfer through textile respectively. Then we obtain the numerical solution of temperature and the rate of condensation by finite difference method (FDM). Numerical simulation is achieved for down and polyester material in order to verify the validity of methods. The numerical results are well matched with the experimental data on the “Walter” Manikin.